2011
DOI: 10.1038/oby.2011.16
|View full text |Cite
|
Sign up to set email alerts
|

Elevated BMI Is Associated With Decreased Blood Flow in the Prefrontal Cortex Using SPECT Imaging in Healthy Adults

Abstract: Obesity is a risk factor for stroke and neurodegenerative disease. Excess body fat has been linked to impaired glucose metabolism, insulin resistance, and impulsivity and may be a precursor to decline in attention and executive cognitive function. Here, we investigated the effects of high BMI on regional cerebral blood flow (rCBF) using single photon emission computed tomography (SPECT) imaging in healthy subjects. A total of 16 adult men and 20 adult women were recruited from the community between January 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
6
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(158 citation statements)
references
References 14 publications
7
142
6
3
Order By: Relevance
“…But a recent study found no such abnormalities when a correction for the commonly in AN reduced brain volume was applied (Bailer et al, 2007), suggesting that baseline blood flow is not reduced. In OB, reduced resting blood flow was found in various frontal cortical brain regions (Willeumier et al, 2011), but that study did not correct for brain volume. As OB has been associated with reduced brain GM volumes (Gunstad et al, 2008), reduced regional brain blood flow in OB is not certain, and the found blood-flow reduction may have disappeared if a partial volume correction had been applied, similarly to the results in AN.…”
Section: Limitationsmentioning
confidence: 99%
“…But a recent study found no such abnormalities when a correction for the commonly in AN reduced brain volume was applied (Bailer et al, 2007), suggesting that baseline blood flow is not reduced. In OB, reduced resting blood flow was found in various frontal cortical brain regions (Willeumier et al, 2011), but that study did not correct for brain volume. As OB has been associated with reduced brain GM volumes (Gunstad et al, 2008), reduced regional brain blood flow in OB is not certain, and the found blood-flow reduction may have disappeared if a partial volume correction had been applied, similarly to the results in AN.…”
Section: Limitationsmentioning
confidence: 99%
“…Sequelae of chronic hyperlipidemia and poor glycaemic control, and of manifest hypertension and diabetes, likely contribute to, and cause deficits across a variety of cognitive domains [65,66] including attention, processing speed, memory, and executive functioning [67,68]. Overweight and obesity significantly reduce regional cerebral blood flow, specifically to the prefrontal cortex, negatively impacting behaviors associated with the PFC [69];…”
Section: Obesity Worsens Np-and Functional Deficitsmentioning
confidence: 99%
“…In otherwise mentally healthy individuals, elevated body mass index (BMI) has independently been associated with reduced cognitive performance [62], related to changes in brain structure and function [63], and reduced decision making capacity [64]. Sequelae of chronic hyperlipidemia and poor glycaemic control, and of manifest hypertension and diabetes, likely contribute to, and cause deficits across a variety of cognitive domains [65,66] including attention, processing speed, memory, and executive functioning [67,68].…”
Section: Obesity Worsens Np-and Functional Deficitsmentioning
confidence: 99%
“…1 Data from the World Health Organization suggest that overweight and obesity lead to health consequences such as cancers, cardiovascular disease and metabolic disease. 2 Recent studies have suggested that obesity is an important predictor of structural brain impairments, 3 abnormal brain function 4 and decreased behavioral performance in tests of executive function (EF). 5 Body mass index (BMI) has been widely used in previous studies as a sole marker of obesity.…”
Section: Introductionmentioning
confidence: 99%